TECHNOLOGY OF CREATION OF THEMATIC COMPOSITION BASED ON INTERPRETATION OF COMPOSITION ISSUES IN PAINTING (American Journal of Research in Humanities and Social Sciences, 2024)
This article reveals the technology of working with some basic and auxiliary techniques and elements when creating compositional thematic works in painting.